EVALUASI GUIDELINE DAN E-LEARNING DIGITAL LITERACY MENGGUNAKAN MODEL CIPP - Anestya Ayunda, Winda; Nurhadryani, Yani; Wijaya, Sony (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2020)
This study aims to evaluate digital literacy guidelines based on blended learning using the CIPP model (Contexts, Inputs, Processes, Products). The research method is simple experimental, namely by distributing questionnaires to users who have carried out trials on the system. The source of research data is librarians in the Center for Scientific Documentation and Information. Evaluation is measured by looking at the agreement and disagreement of users regarding the topic of training, completeness of the material, training time, and system quality. The results of the study show that the guidelines and e-learning are declared quite effective. However, there are still some disadvantages, among others, that there is still a small format of teaching material in applications, such as visual content, namely images, videos and audio to be used as reference for learning. In addition, an evaluation of the timing of training is needed.